Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0253456
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human amnion epithelial cells on lung development and inflammation in preterm lambs exposed to antenatal inflammation

Abstract: Background Lung inflammation and impaired alveolarization are hallmarks of bronchopulmonary dysplasia (BPD). We hypothesize that human amnion epithelial cells (hAECs) are anti-inflammatory and reduce lung injury in preterm lambs born after antenatal exposure to inflammation. Methods Pregnant ewes received either intra-amniotic lipopolysaccharide (LPS, from E.coli 055:B5; 4mg) or saline (Sal) on day 126 of gestation. Lambs were delivered by cesarean section at 128 d gestation (term ~150 d). Lambs received int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Namely, the improvement of lung function was preceded by enhanced acinar development after MAPC therapy, designated by increased RAC and TTF-1+ cells in LPS-exposed and MAPC-treated animals, indicating that an improved lung architecture in concert with the reduction of edema is responsible for the improvement of lung function. This concept is supported by earlier findings showing that MSC treatment accelerated pulmonary growth and regeneration in injured preterm lungs of mice and sheep [ 17 , 45 ]. For instance, a preterm lamb model of antenatal inflammation reported improved alveolar development by endorsing alveolar growth and differentiation after MSC treatment [ 17 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Namely, the improvement of lung function was preceded by enhanced acinar development after MAPC therapy, designated by increased RAC and TTF-1+ cells in LPS-exposed and MAPC-treated animals, indicating that an improved lung architecture in concert with the reduction of edema is responsible for the improvement of lung function. This concept is supported by earlier findings showing that MSC treatment accelerated pulmonary growth and regeneration in injured preterm lungs of mice and sheep [ 17 , 45 ]. For instance, a preterm lamb model of antenatal inflammation reported improved alveolar development by endorsing alveolar growth and differentiation after MSC treatment [ 17 ].…”
Section: Discussionsupporting
confidence: 81%
“…At 132 dGA, fetuses were surgically delivered, which was followed by oral intubation with an endotracheal tube, umbilical cord clamping and the lambs were weighted. Lambs were transitioned to an infant radiator bed (IW930 Series, Cosy-Cots™ Infant Warmer, Fisher&Paykel, Auckland, NZ), where they were dried and placed in a sling [ 17 ]. The lamb was immediately connected to an infant ventilation device (Fabian HFO®; Acutronic, Hirzel, CH) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intra-amniotic administration of LPS at E16.5 to induce in ammatory cascades-CAM is similar to the major clinical characteristics observed in patients with BPD. CAM can produce excessive in ammatory factors into the fetus, which affect the maturation of fetal lung, cause fetal lung structural remodeling, affect the contractile function of pulmonary vessels, and thus lead to the occurrence of BPD [21,22]. Our results indicated that LPS group exhibited a disorder of intrauterine development: the intrauterine fatal death (IUFD) rates represented a high level in the LPS group.…”
Section: Discussionmentioning
confidence: 71%
“…However, the model still has drawbacks such as complex experimental operations, significant trauma, and susceptibility to infection. CAM can produce excessive inflammatory factors in the fetus, which affect the maturation of the fetal lung, cause fetal lung structural remodeling, and affect the contractile function of pulmonary vessels, thus leading to the occurrence of BPD [ 19 , 20 ]. Our results indicated that the LPS group exhibited a disorder of intrauterine development: intrauterine fetal death (IUFD) rates were high in the LPS group.…”
Section: Discussionmentioning
confidence: 99%